(untitled) (Eurasian Journal of Learning and Academic Teaching, 2025)
The use of Suggestopedia as a teaching methodology for English as a Second Language (ESL) is examined in this article. It examines the fundamental ideas of Suggestopedia, its evolution throughout time, and its purported advantages as well as drawbacks. The results of sample study are then examined in order to determine how well it works in comparison to more traditional approaches in terms of enhancing language acquisition, learner motivation, and the general classroom environment. The conversation examines Suggestopedia’s advantages and disadvantages and makes recommendations for future study and real-world implementation. In order to optimize Suggestopedia’s potential advantages in a variety of ESL contexts, the conclusion highlights the necessity of cautious implementation and teacher training